Oral free and dipeptide forms of glutamine supplementation attenuate oxidative stress and inflammation induced by endotoxemia - Cruzat, Vinicius; Bittencourt, A.; Scomazzon, S.; Leite, J.; de Bittencourt Jr, P.; Tirapegui, J. (Elsevier Inc., 2014)
Objective: The aim of the present study was to determine the effects of oral supplementation with L-glutamine plus L-alanine (GLN+ALA), both in the free form and L-alanyl-L-glutamine dipeptide (DIP) in endotoxemic mice. Methods: B6.129 F2/J mice were subjected to endotoxemia (Escherichia coli lipopolysaccharide [LPS], 5 mg/kg, LPS group) and orally supplemented for 48 h with either L-glutamine (1 g/kg) plus L-alanine (0.61 g/kg) (GLN+ALA-LPS group) or 1.49 g/kg DIP (DIP-LPS group). Plasma glutamine, cytokines, and lymphocyte proliferation were measured. Liver and skeletal muscle glutamine, glutathione (GSH), oxidized GSH (GSSG), tissue lipoperoxidation (TBARS), and nuclear factor (NF)-κB–interleukin-1 receptor-associated kinase 1 (IRAK1)–Myeloid differentiation primary response gene 88 pathway also were determined.Results: Endotoxemia depleted plasma (by 71%), muscle (by 44%), and liver (by 49%) glutamine concentrations (relative to the control group), which were restored in both GLN+ALA-LPS and DIP-LPS groups (P < 0.05). Supplemented groups reestablished GSH content, intracellular redox status (GSSG/GSH ratio), and TBARS concentration in muscle and liver (P < 0.05). T- and B-lymphocyte proliferation increased in supplemented groups compared with controls and LPS group (P < 0.05). Tumor necrosis factor-α, interleukin (IL)-6, IL-1 β, and IL-10 increased in LPS group but were attenuated by the supplements (P < 0.05). Endotoxemic mice exhibited higher muscle gene expression of components of the NF-κB pathway, with the phosphorylation of IκB kinase-α/β. These returned to basal levels (relative to the control group) in both GLN+ALA-LPS and DIP-LPS groups (P < 0.05). Higher mRNA of IRAK1 and MyD88 were observed in muscle of LPS group compared with the control and supplemented groups (P < 0.05). Conclusion: Oral supplementations with GLN+ALA or DIP are effective in attenuating oxidative stress and the proinflammatory responses induced by endotoxemia in mice.